Albanian Issue and American Diplomacy in the Paris Peace Conference in the Light of New Historical Sources - Peza, Majlinda; Morina, Andriola (Richtmann Publishing, 2012)
Through the accumulation of the facts and the interpretation of the historical sources, this scientific work tends to givea full picture of the valuable contribution of american diplomacy, itâ€™s representative at the Paris Peace Conference, presidentWilson and american public opinion toward the albanian issue in the years 1919 â€“ 1920. In respect of this approach, we haveseen a period of extraordinary awareness of the american press of the time in favor of the albanian issue, direct result of thevaluable contribution of the albanian diaspora in USA., organized in the federation â€œhearthâ€. simultaneously, as a representativeof this federation, we have to mention the direct commitment and contribution in defense of the albanian issue, Fan S. Noli,which is evidenced in his meeting with president Wilson, taking his promise which he will make a reality in the Paris PeaceConference. This research will be based on analysis of historical resources before and after years â€˜90, seeing from comparativecontext.